Lacan’s Sinthome; or, the Point of Psychoanalysis - Edward Dioguardi (EJP import test, 2020)
Summary: Lacan began his seminar on Joyce saying that “sinthome is an old way of spelling what was subsequently spelt symptome,” with no direct explanation of the “meaning” of these spellings or their origins seeming to follow (Lacan 2016, p. 3). Rather, Lacan, like Joyce, repeatedly puns on the “letter” of the words over and over. Oddly enough “for someone who plays strictly on language,” Joyce can be seen to reduce language to what it produces by way of effect, “when one does not analyze” this very effect (Lacan 2016, p. 146). What language produces here – and what Joyce presents – is the sinthome. Even stranger for psychoanalysis (a practice whose etymological roots lie in a Greek word meaning “loosen”), what Lacan presents is that which Joyce puts forth or nominates – along with his name – as impossible to analyze; or, a knot not-to-be loosened or analyzed.
Keywords: Father; Master; Phallus; Point; Sinthome